The diagnostic analysis of the fault coupling effects in planet bearing. (January 2020) - Xue, Song; Wang, Congsi; Howard, Ian; Lian, Peiyuan; Chen, Gaige; Wang, Yan; Yan, Yuefei; Xu, Qian; Shi, Yu; Jia, Yu; Zheng, Yuanpeng; Wang, Na
Highlights: The planet bearing with different fault combination effect has been investigated. A 34° of freedom planetary gear model with detailed planet bearing model was developed. The models for different bearing fault scenarios and their combinations have been developed. The amplitude modulation of the instantaneous angular speed was used to analyze the results. The coherence estimation has been proposed to quantify the fault impact contribution. Abstract: The purpose of this paper is to investigate the fault coupling effects in the planet bearing as well as the corresponding vibration signatures in the resultant vibration spectrum. In a planetary gear application, the planet bearing can not only spin around the planet gear axis, but also revolve about the sun gear axis and this rotating mechanism poses a big challenge for the diagnostic analysis of the planet bearing vibration spectrum. In addition, the frequency component interaction and overlap phenomenon in the vibration spectrum caused by the fault coupling effect can even worsen the diagnosis results. To further the understanding of the fault coupling effects in a planet bearing, a 34° of freedom planetary gear model with detailed planet bearing model was established to obtain the dynamic response in the presence of various bearing fault scenarios. The method of modelling the bearing distributed faults and localized faults has been introduced in this paper, which can be further incorporated into the planetary gear model to obtain the faulted vibration signal. The "benchmark" method has been adopted to enhance the planet bearing fault impulses in the vibration signals and in total, the amplitude demodulation results from 20 planet bearing fault scenarios have been investigated and analyzed. The coherence estimation over the vibration frequency domain has been proposed as a tool to quantify the fault impact contribution from different fault modes and the results suggested that the outer raceway fault contributes most to the resultant planet bearing vibration spectrum in all the investigated fault scenarios.